Investigation of the Propagation Characteristics of Magnetostatic Surface Waves in a Layered Structure of Left-Handed Materials (LHM) and ferrite (YIG) - Shawqi Mansourr; Mohammed Shabat; Majdi Hamada; Sameer Yassin (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The characteristics of magnetostatic surface waves at microwave frequencies in a layered structure of left-handed material film and a semi-infinite linear ferrite substrate have been investigated. The general dispersion relation is derived and analyzed numerically. It is found that it has two solutions for ω(k), one represents a physical solution and other unacceptable. The effects of the applied external magnetic field around the proposed region have also been examined. Keywords: left-handed materials; dispersion relation; magnetostatic surface waves; wave-guides; boundary conditions.